Buckling and crushing behavior of foam-core hybrid composite sandwich columns under quasi-static edgewise compression - Arameh Eyvazian (16500978) (2019)
Buckling and crushing behavior of foam-core hybrid composite sandwich columns under edgewise compressive load is dealt in this study. Composite laminates with different stacking sequence configurations made of glass and Dyneema-woven fabrics and AL 2024-T3 sheets were used in combination of polyvinyl chloride foam core to manufacture the specimens. Effects of face sheet thickness and stacking sequence configuration, slenderness ratio, boundary conditions, and sandwich reinforcement with through-thickness resin pins on the buckling and crushing behavior of the specimens were investigated. The results revealed that using the resin pins changes the unstable Euler buckling mode to a more stable progressive end-crushing and significantly increases the buckling load, specific buckling load, and energy absorption capability, which are highly favorable. Also, the results showed that in the specimens with fiber metal laminates, the major failure modes are face sheet-core debonding and face sheet delamination. However, based on the results, specimen with hybrid face sheets made from Dyneema fabrics and aluminum plates has the highest buckling load as well as the highest specific buckling load. Also, a specific fixture was designed to laterally clamp the sandwich column which causes a reduction in the probability of specimen end-crushing and significantly increases the buckling load. Other Information Published in: Journal of Sandwich Structures & Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/1099636219894665